Effect of molasses based multi-nutrient herbal supplements on hematobiochemicals, serum lipid, antioxidants and hormonal profile in buffalo calves - KUMARI, PUNITA; SINGH, P; VERMA, A K; GAUR, G K; DAS, A (The Indian Journal of Animal Sciences, 2020)
Effect of molasses based multinutrients herbal supplements (MMS) containing ground fenugreek seed and deoiled mahua seed cake at two different ratios (1:1; MMS-I or 1:3; MMS-II) on hematobiochemicals, serum lipid, antioxidants and hormonal profile in male buffalo calves was assessed for 9 months. Fifteen male Murrah buffalo calves (10 to 15 months of age and mean body wt. 234–236 kg) were randomly distributed into 3 groups (5 each) according to Randomized Block Design (RBD). All animals were fed individually with conventional concentrate mixture, available green fodder (3–4 kg DM/d) and wheat straw ad lib. to meet out nutrients requirement. While animals in control group (C) were fed no supplement but animal’s diet in group T1 and T2 supplemented with MMS-I and MMS-II, respectively at 44 g/100 kg body weight or 200 g /100 kg metabolic body weight (kgW0.75). The values of Hb, PCV, RBC, WBC, platelets count, serum total protein, uric acid, creatinine, urea level, total cholesterol, triglyceride, high density lipoprotein (HDL) and T3 hormone level were comparable among 3 groups. Serum glucose, globulin, antioxidants and testosterone levels were significantly increased but serum albumin, A/G ratio, low density lipoprotein (LDL) and cortisol levels were significantly decreased among supplemented groups as compared to control group and hormone T4 was significantly higher in T1 group. The results showed that supplementation of MMS-I and MMS- II in the diet of buffalo calves improved serum glucose, globulin, antioxidants, T4 and testosterone levels but lower albumin, A/G ratio, LDL and cortisol.